The concept of CSR in accounting theory and practice in Poland: an empirical study - Małgorzata Macuda (Zeszyty Teoretyczne Rachunkowości, 2015)
Purpose. Right now, the issue of Corporate Social Responsibility (CSR) lies within the scope of interest of various fields of social science and practice, including the science and practice of accounting. Numerous research works stress how accounting, particularly in terms of corporate reporting, is closely connected to the concept of CSR. The number of studies concerning especially CSR reporting has increased in recent years all over the world, but in Poland CSR reporting is a new field not yet covered by many current research papers. The main purpose of this work is to present the concept of CSR in the theory and practice of accounting. Design/methodology/approach. The research paper comprises a literature review and a content analysis. The literature review was conducted in the first part of the work, which was devoted to the presentation of the idea of corporate social responsibility in the context of accounting and corporate reporting, and also in the second part, which contains an overview of the most well-known and comprehensive global standards related to CSR reporting. The content analysis was used in the final part of the work to examine the disclosures of CSR in annual reports and separate reports (Management commentary, communications) on a population of Polish stock exchange companies listed on the Warsaw Stock Exchange (WSE) Main Market as of 31 October 2013, which are also listed in the WIG-Poland index and the RESPECT Index –the first Polish, and one of the few European indexes of socially responsible companies. Findings. It has been determined that among Polish public companies listed on the WSE, which are also listed in the WIG-Poland index, only 6% operate in a socially responsible manner according to the RESPECT criteria, and less than 4.6% of all companies listed in the WIG-Poland and 70% of RESPECT index companies prepare separate CSR reports. Out of all the companies that prepare separate CSR reports, 93% prepare ESG reports (Environment, Social, Governance), but to a different scope. Out of all the companies preparing separate CSR reports, 70% followed the GRI Guidelines. The percentage share of companies whose CSR reports were verified by an independent external auditor is not very high –18%. Among the companies that prepared separate CSR reports and are listed in the RESPECT Index, only one prepared an integrated annual report for the year 2012. Research limitations/implications. The authors are aware of the limited subjective scope which might lead to some restrictions when extrapolating the results onto all the companies operating in Poland. Moreover, it cannot be excluded that companies not listed on the WSE also prepare CSR reports. This is why any attempt to apply the conclusions from this study to the general population may lead to erroneous results.